Implementation of Performance Assessment with Assistance to Improve Students' Scientific Written Communication Skills - Surtiyarsih, Sri (Universitas Wiralodra, 2023)
The purpose of this study is to describe how the application of performance appraisal with mentoring and improvement of scientific written communication skills. This study used Classroom Action Research (CAR), which consisted of 2 cycles and was carried out on 35 class VII I SMPN 6 student subjects. The results of this study describe performance appraisal activities with assistance and improvement of scientific written communication skills in general and in all indicators. Thus, it can be concluded that the implementation of performance appraisal with assistance can improve students' scientific written communication skills. Performance assessment is carried out by giving assignments in the form of worksheets (LK), while the assistance steps carried out consist of giving written feedback from the teacher to student worksheets, grouping students based on similar errors, students reading the results of the feedback, the teacher visits the group, debriefing the teacher with students, in groups peer tutors are also carried out, and LK improvement by students. The action step that is considered the most important in influencing the results of the action is the mentoring step, namely grouping students based on similar errors. The increase in scientific written communication that scored ≥ 70 from cycle 1 (63.89%) to cycle 2 (97.14%) was 33.25%. This increase is also supported by an increase in each scientific written communication indicator, namely those who get a score of ≥ 75 for the 1st indicator making a description from a graph or table 33.4%, the 2nd indicator changing the description data into a table 5.6%, the 3rd indicator changing data from tables to graphs is 63.9%, the 4th indicator infers from data in the form of tables or graphs 62.63%. The action step that is considered the most important in influencing the results of the action is the mentoring step, namely grouping students based on similar errors. The increase in scientific written communication that scored ≥ 70 from cycle 1 (63.89%) to cycle 2 (97.14%) was 33.25%. This increase is also supported by an increase in each scientific written communication indicator, namely those who get a score of ≥ 75 for the 1st indicator making a description from a graph or table 33.4%, the 2nd indicator changing the description data into a table 5.6%, the 3rd indicator changing data from tables to graphs is 63.9%, the 4th indicator infers from data in the form of tables or graphs 62.63%. The action step that is considered the most important in influencing the results of the action is the mentoring step, namely grouping students based on similar errors. The increase in scientific written communication that scored ≥ 70 from cycle 1 (63.89%) to cycle 2 (97.14%) was 33.25%. This increase is also supported by an increase in each scientific written communication indicator, namely those who get a score of ≥ 75 for the 1st indicator making a description from a graph or table 33.4%, the 2nd indicator changing the description data into a table 5.6%, the 3rd indicator changing data from tables to graphs is 63.9%, the 4th indicator infers from data in the form of tables or graphs 62.63%.